2023
DOI: 10.1073/pnas.2301366120
|View full text |Cite
|
Sign up to set email alerts
|

The liquid-to-solid transition of FUS is promoted by the condensate surface

Abstract: A wide range of macromolecules can undergo phase separation, forming biomolecular condensates in living cells. These membraneless organelles are typically highly dynamic, formed reversibly, and carry out essential functions in biological systems. Crucially, however, a further liquid-to-solid transition of the condensates can lead to irreversible pathological aggregation and cellular dysfunction associated with the onset and development of neurodegenerative diseases. Despite the importance of this liquid-to-sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…However, recent theories point to the possible gradual transformation of initially homogeneous FUS LLPS condensates to a liquid-core/gel-shell architecture through aging . A new experimental study supported this notion for the nonagitated aging of FUS condensates, suggesting the gradual solidification of the condensate surface over several days through a dissolution assay . Separately, tracing individual gold nanorods in TFEB condensates has indicated reduced mobilities at the condensate surface .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, recent theories point to the possible gradual transformation of initially homogeneous FUS LLPS condensates to a liquid-core/gel-shell architecture through aging . A new experimental study supported this notion for the nonagitated aging of FUS condensates, suggesting the gradual solidification of the condensate surface over several days through a dissolution assay . Separately, tracing individual gold nanorods in TFEB condensates has indicated reduced mobilities at the condensate surface .…”
Section: Discussionmentioning
confidence: 94%
“…For example, for single-component LLPS condensates, whereas it is common to assume that each microdroplet adopts a homogeneous phase, recent theoretical and experimental work points to potential intracondensate inhomogeneity, e.g., the gradual transformation of FUS LLPS condensates to liquid-core/gel-shell multiphase architectures through aging. 19,25 The detection and elucidation of possible nanoscale heterogeneities in the often micrometer-sized condensate droplets are impeded by the ∼300 nm resolution of diffraction-limited optical microscopy. The past decade has seen substantial advances in super-resolution microscopy (SRM), including single-molecule localization microscopy (SMLM), which, by superlocalizing the positions of millions of individual molecules over consecutive camera frames, routinely achieves ∼20 nm spatial resolution.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms for primary and secondary nucleation apply to both proteins and peptides, while the aggregation pathway for short peptides is slightly different and a higher reaction rate is expected, as the β-strands are directly exposed to the environment and not hindered by higher-level secondary and tertiary structures. Recent studies have shown that a wide range of proteins and peptides can first undergo a rapid liquid–liquid phase separation to form molecule-rich condensates due to weak molecular interactions, and then undergo a liquid-to-solid transition to form self-assembled fibrillar structures as a result of strong molecular interactions. Interestingly, the transitions are rapid for short peptides such as z-FF (carboxybenzyl-protected diphenylalanine). The whole process lasts within an hour. , For longer peptides such as TPPGFF, and whole proteins such as FUS (FUsed in Sarcoma), the condensates are formed within minutes and converted to ordered solid structures within days. , As is clear from the mechanism described here, the self-assembly process is strongly related to the interaction between the protein molecules.…”
Section: Fibrillation Mechanismsmentioning
confidence: 99%
“…Recent studies have shown that a wide range of proteins and peptides can first undergo a rapid liquid–liquid phase separation to form molecule-rich condensates due to weak molecular interactions, and then undergo a liquid-to-solid transition to form self-assembled fibrillar structures as a result of strong molecular interactions. Interestingly, the transitions are rapid for short peptides such as z-FF (carboxybenzyl-protected diphenylalanine). The whole process lasts within an hour. , For longer peptides such as TPPGFF, and whole proteins such as FUS (FUsed in Sarcoma), the condensates are formed within minutes and converted to ordered solid structures within days. , As is clear from the mechanism described here, the self-assembly process is strongly related to the interaction between the protein molecules. This interaction can be influenced by both intrinsic properties and external constraints, as discussed in the following sections.…”
Section: Fibrillation Mechanismsmentioning
confidence: 99%